Safety of historical stone arch bridges - Proske, Dirk.; Gelder, Pieter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
Historical stone arch bridges are still a major part of the infrastructure in many countries. Although this type of bridge has proven to be an efficient construction type, it often poses the problem of insufficient numerical models of the load bearing behavior. Therefore the book introduces methods to adapt life loads and introduces different types of numerical models of the load resistance respectively. The book continues with the introduction of specific damages and strengthening techniques. The book particularly focuses on the probabilistic safety assessment of historical arch bridges, for which often only limited material and structural data is available.
Loads -- of Historical -- Masonry Strength -- Investigation Techniques -- Damages and Repair -- Safety Assessment -- Examples.
Keywords: Engineering; Construction; Buildings -- Design and construction; Building; Engineering, Architectural; Building materials; Building repair; Buildings -- Repair and reconstruction; Engineering; Building Repair and Maintenance; Building Construction; Building Materials; Basics of Construction; Electronic books